An intelligent Hybrid Wind–PV farm as a static compensator for overall stability and control of multimachine power system. (April 2022) - Kumar, Rajeev; Diwania, Sourav; Singh, Rajveer; Ashfaq, Haroon; Khetrapal, Pavan; Singh, Sheetal
Abstract: The paper demonstrates the potential of a hybrid Wind–PV farm as STATCOM (Static Synchronous Compensator) for damping and control of overall chaotic oscillations in a two-area power system. Kundur's modified system associated with a hybrid Wind–PV farm is simulated in MATLAB to demonstrate the detailed performance assessment of the hybrid farm. A unique controller is deployed to regulate the AC and DC currents of the STATCOM using two PI controllers. A swarm-based hybrid metaheuristic optimizer PSO-BFOA optimally tunes and controls the PI controller parameters. The system is compensated to an optimum level of 85% and exposed to a 3-phase fault. Zero dampings are accompanied by additional disturbances of a 20% change in electric torque and the reference voltage. The disturbances are made to model the worst conditions to examine the rigorous performance of the hybrid Wind–PV​ farm in alleviating the overall chaotic oscillations. The simulation results for the performance assessment in different cases, i.e., without control, with Wind-STATCOM, with PV-STATCOM, and with the hybrid Wind–PV-STATCOM, reveal the potential of the hybrid Wind–PV Farm as STATCOM in alleviating the overall chaotic oscillations. Graphical abstract: Highlights: An intelligent hybrid Wind–PV-STATCOM enhances the overall stability of the power system. The gate signal in the Wind–PV-STATCOM is controlled using a unique control scheme. The potential of the Wind, PV, and hybrid Wind–PV-STATCOM has been compared and demonstrated.